Outcomes of Open Reduction and Modified McLaughlin’s Procedure in Neglected Posterior Shoulder Dislocation - Vikas; Jatin Prakash; Karan Maggo; Jujhar Singh; Ankesh Jain; Naval Bhatia (Journal of Orthopedics, Traumatology and Rehabilitation)
Introduction: Neglected posterior glenohumeral joint (GHJ) dislocation is a rare and challenging injury that often goes untreated for an extended period. This condition poses diagnostic and therapeutic difficulties, leading to long-term complications if left untreated. Accurate diagnosis requires a high index of suspicion and comprehensive evaluation, including radiographic imaging and additional modalities such as computed tomography (CT) scans and magnetic resonance imaging (MRI). The management of neglected posterior GHJ dislocation is complex, ranging from conservative measures to surgical intervention. This study aims to investigate the clinical outcomes of open reduction supplemented with modified McLaughlin’s procedure for neglected posterior GHJ dislocation and identify factors associated with successful outcomes. Methods: This prospective, single-center study included 13 patients who underwent open reduction with a modified McLaughlin’s procedure for chronic posterior shoulder dislocation with humeral head defects. The study was carried out between April 2017 and January 2022. Inclusion criteria were chronic posterior dislocation of the shoulder presenting more than 6 weeks after injury and humeral defect (reverse Hill–Sachs) <30%. Exclusion criteria included associated proximal humerus fractures, severe cartilage damage on MRI, and humeral defect >30%. Preoperative and postoperative clinical and imaging evaluations were performed, including radiographs, CT scans, and MRI. Outcome measures included range of motion, Constant Shoulder Score, and Disability of Arm, Shoulder, and Hand (DASH) score. Statistical analyses were conducted using paired t-tests and independent sample t-tests. Results: The study included 13 patients (4 females, 9 males) with a mean age of 40.69 years and a mean delay of 8.5 weeks from injury to diagnosis. The average follow-up period was 18 months. The Constant Shoulder Score significantly improved from a mean score of 51 preoperatively to a mean score of 90 at 1-year follow-up (P < 0.001). Similarly, the DASH score improved from a mean of 78 preoperatively to a mean of 15 postoperatively at 1-year follow-up (P < 0.001). Pain was mainly experienced during strenuous physical activity, and functional limitations were minimal. Strength and range of motion in the treated limbs were satisfactory, with good stability observed in all treated shoulders. Radiographic evaluation did not reveal anatomical misalignment or associated lesions. Conclusion: Open reduction supplemented with modified McLaughlin’s procedure shows favorable outcomes in patients with neglected posterior GHJ dislocation. The procedure leads to significant improvements in Constant Shoulder Scores, pain relief, functional recovery, and shoulder stability. Early diagnosis and timely surgical intervention are crucial in achieving successful outcomes for neglected shoulder dislocations. Further studies with larger sample sizes and longer follow-up periods are warranted to validate these findings and optimize treatment approaches.